Limits on the Detection of Transients Imposed by Scattering - Macquart, Jean-Pierre (Scuola Internazionale Superiore di Studi Avanzati (S I S S A), 2007)
Three scattering mechanisms that limit the observable properties low-frequency emission from transient sources are discussed. Both Induced Compton and Induced Raman scattering potentiallyhinder the escape of the bright radiation envisaged to be generated from the compact extragalactic transients and that many hope to detect with future widefield radio telescopes. In cases where the radiation is observed, they constrain the nature of the mechanism responsible for the emission. Scattering in the Intergalactic Medium is a potentially powerful tool for probing the structure of all the ionized baryons in the IGM (in which most of the baryonic mass of the universe resides at z<7), but is also likely to strongly hinder the observability of short-timescale events at frequencies below ~ 300MHz. We apply this scattering physics to the transient recently reported by Lorimeret al. and discuss with the duration of the event is likely dominated by scattering in the IGM and not the local ISM. If this is the case, it implies that turbulence exists in the IGM down to scales less than ~ 7x 10 7m, and a simple argument suggests that the magnetic field in the IGM scattering region is >4(Te/10 3K)1/2 nG.